Physiological and Physical Profile of Taekwondo Athletes of Different Age Categories During Simulated Combat - Muñoz-Arias, E; Herrera-Valenzuela, T (Idokan Poland Association, 2014)
The purpose of the present study was to compare the physiological responses and the actions performed by taekwondo athletes from three different age groups. The sample consisted of children (10.9 ± 1.6 years), cadets (14.7 ± 1.3 years) and adults (23.4 ± 3.1) male taekwondo athletes, who participated in simulated taekwondo competition. Higher values were found in blood lactate cadets (9.49 ± 3.52 mmol. L-1) versus children (5.87 ± 2.45 mmol. L-1;, n2 = 0.274, P = 0.01), lower displacement values in adults (166.7 ± 20.2 m) versus children (225.4 ± 39.6 m, n2 =0.265, P = 0.01). Maximum speed also differed among groups (F = 3.39; P = 0.048; ?2 = 0.195), with lower values for children (1.89 ± 0.22) versus adults (2.19 ± 0.34, P = 0.041) and cadets (2.16 ± 0.34, P = 0.025). For peak heart rate (HRpeak) there was an effect of group (F = 4.14; P = 0.027; ?2 = 0.24) and of round (F = 10.55; P = 0.001; ?2 = 0.28). Cadets had a higher HRpeak compared to adults (P = 0.025). Independently of age group, round 1 resulted in lower HRpeak compared to both rounds 2 (P = 0.004) and 3 (P < 0.001). Blood lactate, displacement, maximum speed and HRpeak differed among age groups, with no difference in acceleration and number of impacts. HRpeak and HRmean differed among rounds. The time spent during match simulated differed among HRpeak zones. © Id?kan Poland Association.